2012
DOI: 10.1007/jhep11(2012)092
|View full text |Cite
|
Sign up to set email alerts
|

A simple grand unified relation between neutrino mixing and quark mixing

Abstract: It is proposed that all flavor mixing is caused by the mixing of the three quark and lepton families with vectorlike fermions in 5 + 5 multiplets of SU (5). This simple assumption implies that both V CKM and U MN S are generated by a single matrix. The entire 3 × 3 complex mass matrix of the neutrinos M ν is then found to have a simple expression in terms of two complex parameters and an overall scale. Thus, all the presently unknown neutrino parameters are predicted. The best fits are for θ atm < ∼ 40 • . The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…The model of flavor symmetry and flavor violation proposed in [1] has the virtue that it is (a) conceptually simple, (b) explains some of the qualitative features of the quark and lepton spectrum (e.g. the MNS angles being much larger than the CKM angles), and (c) is highly predictive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The model of flavor symmetry and flavor violation proposed in [1] has the virtue that it is (a) conceptually simple, (b) explains some of the qualitative features of the quark and lepton spectrum (e.g. the MNS angles being much larger than the CKM angles), and (c) is highly predictive.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore there are four predictions, which we may take to be (M ν ) ee (which comes into neutrino-less double beta decay), and the three CP-violating phases. In [1], it is found that the model's best-fit values are δ Dirac = 1.15π radians, and (M ν ) ee = 0.002 eV. But the model actually is considerably more predictive than counting parameters suggests, due to the fact that the expressions for observables in terms of model parameters are very non-linear.…”
Section: Jhep08(2015)144mentioning
confidence: 98%
See 2 more Smart Citations
“…Another interesting class of models proposed recently in Ref. [38,39] has a very similar structure for the mass matrices, which we shall not investigate here. We do analyze the flavor U (1) models as special cases of the general class of models described here, which are described next.…”
Section: Anarchy and Hierarchy Via Mixing With Vector-like Fermionsmentioning
confidence: 99%